Growth performance, nutrient digestibility and serum growth hormone level of crossbred boer goats fed with outdoor-grown hydroponic maize fodder - Lim, Whay Chuin (2021)
In recent years, the Boer goats have been imported in large numbers into Malaysia to fulfill the local market demand. Crossbred Boer goats were wellknown for their rapid growth, excellent meat quality, good adaptation, kidding percentage, and non-seasonal fertility. Hydroponics plays a significant role as an alternative fodder supply and helps in efficient livestock production. A preliminary study was conducted to identify the nutritive value of hydroponically sprouted maize fodder from two varieties of maize grains (popcorn and feed corn). Using completely randomised design (CRD) with three replications was used in which popcorn was irrigated with clean tap water (P1) and nutrient solution (P2); feed corn irrigated with clean tap water (P3) and nutrient solution (P4). After 24 hours of germination in wet cloths, sprouted maize grains were spread at a rate of 1 kilogram per tray with 1 – 1.5 cm layer thickness. Sevendays green fodders were sampled for chemical analysis. The total yield of 1.5 kg hydroponic maize fodder per kg feed corn was recorded lower than popcorn (2.5 kg per kg grains) per 7-day growth periods along with 20 - 21 cm height. The crude protein content was the highest at 7.48±0.01% in P4 compared to popcorn (P<0.05) and P3 (P>0.05). Treatment 3 showed the highest dry matter content as 94.42±0.13% (P>0.05) and organic matter content observed as 98.29±0.13% especially compared with P1 (P<0.05). The neutral detergent fibre (NDF) and acid detergent fibre (ADF) contents of feed corn were insignificantly different, but P3 was observed as 67.66±00.05% and 41.55±0.04%, respectively, which were higher than P1 (P<0.05). Although feed corn had better nutritional value than popcorn, popcorn showed a higher germination rate for the 7-day germination period, which was 7% higher than feed corn (84.3 ± 0.88%) (P<0.05). Germination of 1 kg popcorn would produce approximately 2.5 kg of fresh fodder (P1 and P2) compared to 1 kg of feed corn that produced about 1.5 kg sprouts (P3 and P4). The use of the nutrient solution for hydroponics fodder production is not mandatory since there is no notable difference in plant height compared with those irrigated with clean tap water throughout the 7-day growth periods. Thus, popcorn with a higher conversion ratio and the germination rate was used in the study to investigate the effects of feeding outdoor-grown hydroponics maize fodder (HMF) on growth performance, nutrient digestibility, and serum growth hormone level in goats. A total of fifteen male crossbred Boer goats of 5.87±2.16 months old with an initial body weight of 17.3±0.88 kg were allocated in a completely randomised design (CRD) to three treatments (n=5). The animals in group T1 (control) were fed 500g commercial concentrate and Napier grass; T2, the animals were fed with 500g commercial concentrate and HMF, while T3 had solely fed with HMF. The study was conducted at a breeding farm in Lendu, Melaka, for 13 weeks after a 2-week adaptation period. The results showed that HMF had a better feed nutritive composition with a lower concentration of highly indigestible fibre (P<0.05) and a higher concentration of crude protein (CP), about 12.28±0.25% compared to CP in Napier grass (7.22±0.09%) (P<0.05). Dietary treatments had significant effects (P<0.05) on the goats' weight gain, feed intake, and feed conversion ratio. Goats in groups T1 and T2 fed with commercial concentrate had higher body weight gain with an average daily gain (ADG) of 79±0.12 g/day and 48±0.01 g/day compared to goats in group T3 (44±0.01 g/day) (P<0.05). Feed intake was the highest (P<0.05) in goats in group T3 due to the sole feeding of HMF, while the lowest intake was in animals 500g commercial concentrate and HMF (T2). Feed conversion ratio (FCR) was improved (P<0.05) in T1 and T2 goats, 14.93±2.18 and 16.62±2.92, respectively. Goats in groups T1 and T2 showed significantly higher dry matter digestibility (69.27±0.95% and 63.95±2.07%, respectively) and crude protein digestibility (71.89±0.20% and 72.28±0.10%, respectively) compared to group T3. The correlation coefficients between the final live weight with height at withers, body length, and chest girth were positive (P<0.01). Generally, the feeding of hydroponic maize fodder in Treatment 2 and Treatment 3 showed a high concentration of growth hormone during Week 1 (P<0.05) and Week 11 (P>0.05) of feeding treatment, respectively. Sole feeding of HMF exerted a minor impact on growth performance in the animals. However, the HMF could potentially replace the conventionally planted sprouts in conjunction with commercial concentrate to improve the growth performance of the small ruminants.